Penerapan e-Management Sebagai Bentuk Efisiensi Tata Kelola Organisasi Pada Yayasan Ponpes Al -Idris Surabaya - Nurul - Azizah; Arimurti Kriswibowo (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The digital era encourages their governance governance are far more effective and efficient. Most large organizations undertake various efforts to adapt in order to megikuti developments that exist. However, there are some organizations that are still limited in terms of knowledge and insight related to technological developments. Pondok Foundation Pesantren al-Idris is one of the institutions of society non-profit that is engaged in the field of education of religion, have limitations related to the ability to adapt to the development of the technology. Though its existence in the middle of the town demanded their governance governance that is good that the existence of the foundation of the more well known in the community area. Yayasan Pesantren al- Idris has the participant students an average age of productive that has potential beyond the ordinary to develop the skills and insights. The purpose of the activities of these is provide insight and pealtihan related to governance governance of the organization via e-Management so that the future is able to generate a source of power mnausia that unggu both in the field of religion and knowledge common are relevant . Event application of science and technology on society will be implemented two phases debriefing wawasn and training in the making of web organization. Then monitoring and evaluation will be carried out so that the sustainability of this activity can be achieved. The output of this activity is being able to become a means of direct participation of academics in fulfilling the tri dharma of higher education. Academic output can produce modules as guidelines for website management by the Al-Idris Surabaya foundation.